Researching Men’s Sheds in Community Contexts in Australia: What does it tell us about Adult Education for Older Men? - Barry Golding (Adult Education Research Conference, 2007)
This paper reports research into community-based men’s sheds in Australia, focusing on how regular activity in these sheds impacts on the informal learning experiences of the mainly older men who use them. It focuses on how men’s learning experiences in sheds informs adult education in community contexts for older men.